'To prevent this disease, we have to stay at home, but if we stay at home, we die of hunger' – Livelihoods, vulnerability and coping with Covid-19 in rural Mozambique. (March 2022) - Krauss, Judith E.; Artur, Luis; Brockington, Dan; Castro, Eduardo; Fernando, Jone; Fisher, Janet; Kingman, Andrew; Moises, Hosia Mavoto; Mlambo, Ana; Nuvunga, Milagre; Pritchard, Rose; Ribeiro, Natasha; et al.
Highlights: Our research traces the differentiated impacts of Covid-19 on the livelihoods of 92 panelists from nine rural communities across Mozambique. Between May and July 2020, weekly phone interviews (n = 441 total) with a diverse panel illustrated the impacts of Covid restrictions. Transport and trading restrictions made market access more difficult or impossible, eliminating or diminishing diverse rural livelihoods. Covid-related restrictions exacerbated socio-economic vulnerabilities such as age, gender, low income, and created new ones. The only diversification strategies which proved effective involved adaptive, socially-minded value-chain partners. Abstract: Non-pharmaceutical interventions (NPIs) such as social distancing and travel restrictions have been introduced to prevent the spread of the novel coronavirus (hereinafter Covid). In many countries of the Global South, NPIs are affecting rural livelihoods, but in-depth empirical data on these impacts are limited. We traced the differentiated impacts of Covid NPIs throughout the start of the pandemic May to July 2020. We conducted qualitative weekly phone interviews ( n = 441) with 92 panelists from nine contrasting rural communities across Mozambique (3–7 study weeks), exploring how panelists' livelihoods changed and how the NPIs intersected with existing vulnerabilities, and created new exposures. The NPIs significantly re-shaped many livelihoods and placed greatest burdens on those with precarious incomes, women, children and the elderly, exacerbating existing vulnerabilities. Transport and trading restrictions and rising prices for consumables including food meant some respondents were concerned about dying not of Covid, but of hunger because of the disruptions caused by NPIs. No direct health impacts of the pandemic were reported in these communities during our interview period. Most market-orientated income diversification strategies largely failed to provide resilience to the NPI shocks. The exception was one specific case linked to a socially-minded value chain for baobab, where a strong duty of care helped avoid the collapse of incomes seen elsewhere. In contrast, agricultural and charcoal value chains either collapsed or saw producer prices and volumes reduced. The hyper-covariate, unprecedented nature of the shock caused significant restrictions on livelihoods through trading and transport limits and thus a region-wide decline in cash generation opportunities, which was seen as being unlike any prior shock. The scale of human-made interventions and their repercussions thus raises questions about the roles of institutional actors, diversification and socially-minded trading partners in addressing coping and vulnerability both conceptually and in policy-making.